2013
DOI: 10.1111/jpc.12277
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the pharyngeal pressure provided by two heated, humidified high‐flow nasal cannulae devices in premature infants

Abstract: Both HHHFNC delivered similar pharyngeal pressures at flow rates of 2-6 L/min. The pressure limiter valve of the Fisher & Paykel device attenuated the pharyngeal pressures at flows of 7 and 8 L/min. Vapotherm trended towards higher delivered pharyngeal pressure at flow rates 7 and 8 L/min, but the clinical significance of the difference remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 13 publications
0
43
0
1
Order By: Relevance
“…Of note, heated high-flow nasal cannula (HHFNC) systems were not in common use at the time. HHFNC, which is reviewed below, delivers an elevated pharyngeal pressure[34] and thus may cause some infants with severe BPD to be incorrectly categorized as having moderate BPD when the clinical FiO 2 is used to determine BPD severity.…”
Section: Overview Of Lung Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, heated high-flow nasal cannula (HHFNC) systems were not in common use at the time. HHFNC, which is reviewed below, delivers an elevated pharyngeal pressure[34] and thus may cause some infants with severe BPD to be incorrectly categorized as having moderate BPD when the clinical FiO 2 is used to determine BPD severity.…”
Section: Overview Of Lung Developmentmentioning
confidence: 99%
“…HHFNC does not require a tight seal and is thus, unlike nCPAP therapy, not associated with nasal trauma [62]. However, as noted above, these devices have been shown to deliver significant positive pharyngeal pressure [34]. Although HHFNC has clinical benefit, providers ought recognize that HHFNC provides significant respiratory support.…”
Section: Overview Of Lung Developmentmentioning
confidence: 99%
“…Although nHF does generate some distending pressure, this varies with gas flow and leak. Despite initial concerns about excessive pressure generation and risk of pneumothorax, most in vivo studies have shown that pharyngeal pressure generated by nHF is (i) similar to, or below, that generated during CPAP and (ii) increases with increased flow rate . Spence et al .…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…For a given flow, the delivered pressure appears to be inversely proportional to an infant's weight, that is, the smallest infants require less flow to generate the same distending pressure as larger infants. One small study compared pressure generated by two nHF devices, Optiflow (Fisher & Paykel, Auckland, New Zealand) and Vapotherm (Vapotherm, Exeter, CA, USA), and showed no pressure differences with flows of 2–6 L/min and slightly higher pharyngeal pressures with Vapotherm at 8 L/min . This may reflect the inclusion of a pressure relief valve in the Optiflow system but not in Vapotherm …”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Collins et al. compared pharyngeal pressures using two commonly used HHFNC devices, the Fisher & Paykel Healthcare HHFNC (Auckland, New Zealand) and the Vapotherm 2000 (Vapotherm Inc., Stevensville, MD, USA), in nine infants at flow rates of 2–8 L/min. There was no difference in pharyngeal pressures recorded between devices at flow rates of 2–6 L/min.…”
Section: Delivery Of Distending Pressurementioning
confidence: 99%